Phonocardiography for Early Detection of Arrhythmia Using Rule-Based Approach - Karomah, Maulida Sri (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2024)
The diagnosis of Arrythmia is primarily made through an Electrocardiogram examination. This test is performed as part of a medical screening, or used to assess the administration of medications or medical procedures on the heart. Another common method for diagnosis of heart abnormalities is through heart sound analysis. Phonocardiography can be used to record sounds produced by the opening and closing of heart valves. This study uses threshold-based and time-based rule-based methods for the detection of S1 and S2 peaks in Phonocardiography signals, estimation of Hear Rate and early detection of Arrhythmia, and improves the implementation of real-time Arrhythmia detection. The HR module has been shown to have high accuracy in detecting heart rate in tachycardia, normal, and bradycardia conditions, with minimal error (0% to 4.1%). The measurement results on mannequins and patients showed a small difference between the HR module and the reference standard. PCG is effective for early detection of arrhythmias as a non-invasive alternative to ECG. Using a rule-based approach and time rule-based system, this system can measure the interval between S1 and S2, and S2 to the next S1 which is then used to calculate the heart rate and can detect arrhythmias in real time. The implication of this study is that the use of PCG integrated with rule-based threshold system can reduce the need for time-consuming and expensive manual ECG analysis. This automated system allows for faster and more accurate diagnosis, providing benefits for real-time arrhythmia monitoring.